2021
DOI: 10.1007/jhep05(2021)292
|View full text |Cite
|
Sign up to set email alerts
|

Chiral gravitational effect in time-dependent backgrounds

Abstract: Gravitational counterpart of the chiral magnetic effect, which is referred as the chiral gravitational effect, can also be of interest in a cosmological setup. In this study, we investigate this effect in the time-dependent chiral asymmetric fermion background and in the expanding spacetime by formulating the effective action of gravitational waves. We also analyze the anomaly equation to see how the backreaction from gravitational waves to thermal chiral plasma occurs. We find that the non-trivial time depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 83 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…(Too large µ 5 causes an apparent catastrophic ghost-like instability, which would not be physical but suggests at least breakdown of the EFT.) For time-dependent µ 5 , a difference in the dispersion relation between the right-and left-handed polarization modes causes an oscillatory memory effect in the time dependence of the µ 5 due to the change of µ 5 induced by the chirality-flipping interaction or the dilution due to the cosmic expansion [290]. Note that at nonzero temperature, it has been indicated that non-local contribution to the induced energy momentum tensor can arise in a non-covariant form [286,287].…”
Section: Chiral Gravitational Wavesmentioning
confidence: 99%
“…(Too large µ 5 causes an apparent catastrophic ghost-like instability, which would not be physical but suggests at least breakdown of the EFT.) For time-dependent µ 5 , a difference in the dispersion relation between the right-and left-handed polarization modes causes an oscillatory memory effect in the time dependence of the µ 5 due to the change of µ 5 induced by the chirality-flipping interaction or the dilution due to the cosmic expansion [290]. Note that at nonzero temperature, it has been indicated that non-local contribution to the induced energy momentum tensor can arise in a non-covariant form [286,287].…”
Section: Chiral Gravitational Wavesmentioning
confidence: 99%
“…Theories characterized by birefringence emerge, therefore, as a candidate where to investigate the possibility that tensor modes could interact non-collisionally with matter. Parity-violating theories are recently receiving increasing attention for their role in modern physics topics such as CMB polarization [63][64][65][66], gravitational waves [67][68][69][70][71][72][73], baryon asymmetry problem [74][75][76][77] and black hole perturbations [78][79][80][81][82][83][84][85][85][86][87]. Among the possible formulations, we mention for instance Holst and Nieh-Yan extensions [88,89], degenerate higher-order scalar-tensor theories (DHOST) [53], Chern-Simons modified gravity (CSMG) [90][91][92][93], bumblebee models [94][95][96][97][98][99][100] and Hořava-Lifshitz gravity [101,102].…”
Section: Introductionmentioning
confidence: 99%
“…[10] for a recent analysis of the already available data). In the context of the early Universe, mechanisms that generate such parity JCAP09(2022)025 violating gravitational waves have been discussed for instance in relation to pseudoscalar (or axion) inflation models with the gravitational topological coupling ϕR µναβ Rµναβ [11][12][13][14][15] or gauge topological coupling ϕF µν F µν [16][17][18] and its non-Abelian version [19][20][21], the existence of chiral fermions [23][24][25], the helical magnetic field [26] due to the chiral plasma instability [27,28], and helical turbulence [29].…”
Section: Introductionmentioning
confidence: 99%